The correspondence - Whitman, Walt, 1819-1892 (Whitman, Walt, 1819-1892. Works. 1961., 2004)
Among the more than one hundred fifty letters collected in this volume are numerous correspondences concerning Whitman's Civil War years, including a letter sending John Hay, the personal secretary to Abraham Lincoln, a manuscript copy of "O Captain, My Captain!" Additional letters address various aspects of the production of Leaves of Grass, the most notable being an extensive correspondence surrounding the Deathbed Edition, gathered by Whitman's friend Horace Traubel, and reproduced here for the first time. Most significantly, this volume at last incorporates Whitman's early letters to Abrah.